Effectiveness of Marketing Public Relations Strategy on the Image of Funding Products at Bank Muamalat KCP Ponorogo - Imelda Sri Agustin; Mohammad Ridwan (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study analyzes the effectiveness of the Marketing Public Relations (MPR) strategy in shaping the image of funding products at Bank Muamalat KCP Ponorogo. The study was motivated by the decline in the number of funding customers in 2025 despite the implementation of various Marketing Public Relations activities. Research Methods: This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the Sub-Branch Manager, Funding Relationship Manager, Customer Service staff, and funding product customers of Bank Muamalat KCP Ponorogo. Data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation. Results: The findings indicate that Bank Muamalat KCP Ponorogo has implemented Marketing Public Relations through seven main tools proposed by Kotler, namely publications, events, sponsorships, news, speeches, public service activities, and identity media. These activities have contributed positively to the image of funding products by increasing customer understanding, creating favorable perceptions, and highlighting the uniqueness of Islamic banking products. However, based on the evaluation model of Cutlip, Center, and Broom, the implementation of Marketing Public Relations has not been fully effective, particularly in encouraging sustainable customer behavior. Conclusion: Marketing Public Relations has succeeded in creating a positive image of funding products but has not been able to consistently maintain customer engagement and long-term usage. Therefore, additional strategies are needed to strengthen customer loyalty and sustain funding product utilization.